Bridging the gap: a case study of a partnership approach to skills development through student engagement in Bristol's Green Capital year. Issue 1 (1st January 2018) - Bigg, Martin; Brooks, Ian; Clayton, William; Darwen, Jamie; Gough, Georgina; Hyland, Fiona; Longhurst, James; Tierney, Ash; Tweddell, Hannah; Walsh, Amy; Willmore, Chris
ABSTRACT: HEIs are well placed to engage with local communities, and can connect students with organisations through several pathways, such as volunteering opportunities, placements, internships, or projects. The University of the West of England, Bristol (UWE), the University of Bristol and their respective Students' Unions have been working in partnership with the city and local communities, using HEFCE Catalyst funding to promote student involvement in sustainability activity during Bristol's year as European Green Capital. The Green Capital Student Capital project has created a broad programme of citywide impact through mobilising the enthusiasm of the city's student body. It delivered a wide-ranging programme of engagement in city sustainability and in so doing developed skills, knowledge and attributes in the student body that support the development of graduate attributes and a more sustainable lifestyle. The project demonstrates how institutions can collaborate across cities and communities to have internal and external impacts for sustainability. Abbreviations: ASHE: Annual Survey of Hours and Earnings; BGCP: Bristol Green Capital Partnership; CBI: Confederation of British Industry; HEFCE: Higher Education Funding Council for England; HEIs: Higher Education Institutions; NUS: National Union of Students; ONS: Office for National Statistics; SME: Small and Medium sized Enterprises; UK: United Kingdom of Great Britain and Northern Ireland; UoB: University of Bristol; UWE: The University of the West of England, Bristol.